ANALYSIS CONSUMER SATISFACTION OF CATFISH SEEDS IN MINA AGROWISATA V MENTAOS VILLAGE, NORTH BANJARBARU DISTRICT - Baturante, Elmiwia Rani; Agusliani, Erma; H.W, Reynaldi Elia (Fish Scientiae, 2025)
Facing increasingly tight competition both grow-out and hatchery-farming farmers, business actors in the fisheries sector continue to strive to innovate both in the technical aspects of cultivation activities and in the areas of services provided to consumers. The aim of this research is to analyze the level of consumer satisfaction catfish seeds in Mina Agrowisata V. The data collection technique used the snowball sampling method and the respondents were cultivators, collectors and consumers/buyers. Data analysis uses the Importance Performance Analysis (IPA) method. The analysis results show that every indicator that influences product quality is on a good and agrotourism service quality is very good scale.